2012
DOI: 10.3844/ajabssp.2012.347.356
|View full text |Cite
|
Sign up to set email alerts
|

DRYING CHARACTERISTICS OF THE BORNEO <i>CANARIUM ODONTOPHYLLUM</i> (DABAI) FRUIT

Abstract: The quality and shelf-life of an underutilized fruits are compromised by the conventional method of drying. We therefore proposed using hot-air chamber to develop the drying curves of Canarium odontophyllum (Dabai) fruit. Present study provides evidence of the best mathematical model to demonstrate the drying characteristics of this indigenous fruit and thus, may generate or add to the existing database. The drying experiments were performed at three different relative humidity of 10, 20 and 30% and a constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The fruit or locally known as "dabai" among the Malaysian has an oblong-shaped with average length of 3 -4 cm, weighing 10 -13 g and is usually consumed as a side meal [10]. The fruit is seasonal being only available during the period from October to December and along with its lack of promotion therefore, the economic potential of the fruit has not been fully explored and utilized [11]. Most of the previous literature reported pharmacological activity on the fruit of C. odontophyllum and until now, there is no past research conducted on the stem bark from C. odontophyllum.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit or locally known as "dabai" among the Malaysian has an oblong-shaped with average length of 3 -4 cm, weighing 10 -13 g and is usually consumed as a side meal [10]. The fruit is seasonal being only available during the period from October to December and along with its lack of promotion therefore, the economic potential of the fruit has not been fully explored and utilized [11]. Most of the previous literature reported pharmacological activity on the fruit of C. odontophyllum and until now, there is no past research conducted on the stem bark from C. odontophyllum.…”
Section: Introductionmentioning
confidence: 99%
“…Much recent research has reported on solar drying of agricultural fruits and vegetables. Thin-layer drying models have also been widely used to analyze the drying of various agricultural [4][5][6][7][8][9][10][11] and marine [12][13][14] products.…”
Section: Introductionmentioning
confidence: 99%
“…Direct solar drying has traditionally been used, except in areas where sunshine is irregular or insufficient and when strict sanitation is required (Ghaly and MacDonald, 2012b). For thermal drying, conduction and convective heat transfer have mainly been used (Basri et al, 2012) as well as radiant heat transfer (Niamnuya et al, 2012). Infrared drying has been investigated for obtaining high quality dried food such as soybean, (Niamnuya et al, 2012), apple (Cuccurullo et al, 2012), rice (Insorn et al, 2010) and fruit leather (Jaturonglumlert and Kiatsiriroat, 2010).…”
Section: Introductionmentioning
confidence: 99%